The Assessment of Circulating 25(OH)D and 1,25(OH)(2)D: Where We Are and Where We Are Going - Hollis, Bruce W. (2007)
The field of vitamin D assay technology has progressed significantly over the past four decades. Further, the clinical utility of these measurements have moved from esoteric into mainstream clinical diagnosis. This movement has been fueled by the realization that vitamin D is involved in bodily systems beyond skeletal integrity. The clinical assay techniques for circulating 25(OH)D and 1,25(OH)(2)D have progressed away from competitive-protein binding assay (CPBA’s) that utilize tritium reporters to radioimmunoassay (RIA’s) that utilize both I(125) and chemiluminescent reporters. These advances have allowed direct serum analysis of 25(OH)D in an automated format that provides a huge sample throughput. Detection of circulating 25(OH)D can also be achieved utilizing direct high performance liquid chromatographic (hplc) or liquid chromatography coupled with mass spectrometry (LC-MS) techniques. These methods are accurate, however, they require expensive equipment and restrict sample throughput in the large clinical laboratory. Direct serum detection of 1,25(OH)(2)D is unlikely to occur for many reasons as a sample pre-purification will always be required. However, a semi-automated chemiluminescent detection system with automated sample preparation is in final development for the determination of circulating 1,25(OH)(2)D. These advances will allow both 25(OH)D and 1,25(OH)(2)D to be detected in an accurate, rapid fashion to meet the clinical demands we see emerging.